Obesity-related venous thromboembolism - Frischmuth, Tobias (UiT The Arctic University of Norway, 2023)
Venous thromboembolism (VTE), a collective term for deep vein thrombosis (DVT) and pulmonary embolism (PE), is a common and multicausal disease. Obesity is a major and likely causal risk factor for VTE. However, to what extent obesity contributes to VTE risk in the general population and the mechanism of obesity-related VTE remain poorly understood. The overall aim of this thesis was (i) to determine the risk of VTE attributed to obesity at population level and (ii) to reveal biomarkers of obesity-related VTE. The study population in all papers was recruited from the 4th-7th surveys of the Tromsø Study (enrolment: 1994-2016), a population-based cohort study. Paper II also included participants from the Trøndelag Health Study (HUNT 2). Exposure information was obtained at survey inclusion through self-administered questionnaires, physical examination, and blood samples. Incident VTE events during follow-up were registered and objectively validated. In paper I, to assess the VTE risk attributed to overweight and obesity, we calculated the population attributable fraction (PAF) using a cohort design and repeated measurements of body mass index (BMI). The PAF of incident VTE due to overweight (BMI 25-30 kg/m2) and obesity (BMI ≥30 kg/m2) was 24.6% (12.9% was attributed to overweight and 11.7% to obesity). In paper II, the joint effect of obesity and established prothrombotic genotypes (rs8176719 in ABO, rs6025 in F5, rs1799963 in F2, rs2066865 in FGG, and rs2036914 in F11) on VTE risk was investigated. Using a case-cohort design, it was observed that the combination of obesity and prothrombotic genotypes, assessed either individually or as a genetic risk score, had an additive effect on VTE risk (i.e., no biological interaction). However, the combination of obesity and some prothrombotic genotypes appeared to have a supra-additive effect on the risk of DVT and unprovoked VTE. In papers III and IV, a nested case-control design was used to investigate whether plasma leptin and plasminogen activator inhibitor-1 (PAI-1) ...